2021
DOI: 10.1002/ece3.7715
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of biochar, nitrogen addition, and microbial agent amendments in remediation of soil properties and microbial community in Qilian Mountains mine soils

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The ammonium nitrogen, available potassium, available phosphorus content, and organic matter content in the soil was increased by the 30 DM treatment. This was consistent with the results in a previous study showing that the addition of the microbial agent neutralized the soil pH and rapidly increased soil nutrient contents [46]. The increase in soil ammonium nitrogen content presumably occurred because the Bacillus subtilis 8-32 was able to fix the N 2 [47].…”
Section: Discussionsupporting
confidence: 92%
“…The ammonium nitrogen, available potassium, available phosphorus content, and organic matter content in the soil was increased by the 30 DM treatment. This was consistent with the results in a previous study showing that the addition of the microbial agent neutralized the soil pH and rapidly increased soil nutrient contents [46]. The increase in soil ammonium nitrogen content presumably occurred because the Bacillus subtilis 8-32 was able to fix the N 2 [47].…”
Section: Discussionsupporting
confidence: 92%
“…Which indicates that biochar application speckled bacterial community composition indirectly through variation in soil properties. A negative correlation between soil pH, MBN and MBC with soil proteobacteria was observed by Kong et al (2021). However, under NPK fertilization, Khan et al (2021) reported a positive correlation of soil proteobacteria with soil N, P and K in sugarcane rhizosphere along with different www.jspae.com (Sun et al, 2021) and after two years in rice field (B) .…”
Section: Relationship Of Soil Proteobacteria With Soil Properties Und...mentioning
confidence: 99%
“…Because biochar is alkaline, its application to the soil can increase soil pH ( Liu, Liu & Zhang, 2014 ). Moreover, the relatively large surface area of biochar addition based on biochar in the short term can improve soil quality by neutralizing soil pH, increasing soil nutrient contents ( Kong et al, 2021 ), and promoting plant growth. In this study, under weakly alkaline soil conditions, adding 3% biochar to the rhizosphere soil of pakchoi resulted in a peak alkaline nitrogen content, a significant increase in soil pH ( Tables 3 and 5 ), and nutrient balance, which was beneficial for the growth and quality improvement of pakchoi.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar amendments can alter plant rhizosphere microbiome, which profoundly affects plant growth and fitness ( Jin et al, 2023 ). Regulation of C/N ratio by adding biochar and N fertilizer affects the composition and diversity of soil bacterial communities ( Kong et al, 2021 ). This study demonstrated that the relative abundance of the bacterial community in pakchoi rhizosphere soil was changed by applying more than 3% biochar.…”
Section: Discussionmentioning
confidence: 99%